Dielectric properties of ferroelectric liquid crystalline material with chiral nematic phase. - Wojciechowski, Marek; Bąk, Grzegorz W.; Tykarska, Marzena (Wydawnictwo Politechniki Łódzkiej, 2015)
The ferroelectric liquid crystal with nematic N* phase has been investigated using broadband low frequency dielectric spectroscopy. The dielectric relaxation modes related to a ferroelectric Goldstone mode were detected only in a narrow temperature range. Well defined relaxation process was detected in the SmB* phase at about 90 Hz.

Dielektryczne badania ferroelektycznego związku ciekłokrystalicznego 1H3R z nematyczną fazą chiralną przeprowadzono w obszarze niskich częstości. Procesy relaksacyjne zarejestrowano jedynie w fazie ferroelektrycznej (mode Goldstona) oraz w fazie SmB* w obszarze częstości 60÷90 Hz. Przedstawiono charakterystyki zarejestrowanych procesów relaksacyjnych.
Dielektryczne własności ferroelektrycznego ciekłego kryształu z chiralną fazą nematyczną.
Institute of Physics, Faculty of Technical Physics, Information Technology and Applied Mathematics. Lodz University of Technology
Instytut Fizyki, Wydział Fizyki Technicznej, Informatyki i Matematyki Stosowanej, Politechnika Łódzka
Centre of Mathematics and Physics, Lodz University of Technology
Centrum Nauczania Matematyki i Fizyki, Politechnika Łódzka
Keywords: dielectric relaxations; ferroelectrics; Goldstone mode; relaksacja dielektryczna; ciekły kryształ; chiralna faza nematyczna; ferroelektryki